Effect of dermal fibroblast conditioned medium on keratinocytes irrespective of age group - Nurul ‘Izzah Abdul Ghani,; Manira Maarof,; Shiplu Roy Chowdhury,; Aminuddin Saim,; Ruszymah Idrus,; Fauzi Mh Busra, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Skin aging causes delayed re-epithelialisation and impaired wound healing. Thus, supplementation of wound healing mediators and extracellular matrix (ECM) components may be a potential treatment strategy for age-related impaired wound healing. Fibroblasts secrete wound-healing factors and can be collected from used medium, i.e., dermal fibroblast conditioned medium (DFCM). In this study, we elucidated the effect of DFCM on the in vitro wound healing of keratinocytes isolated from different age groups (≥18–35, 36–54, ≥55 years) via cell attachment, growth rate, and wound healing rate assays. The DFCM was prepared by culturing confluent fibroblasts with serum-free keratinocytespecific (DFCM-KM) and fibroblast-specific (DFCM-FM) medium. The cell attachment efficiency decreased with the increase of age. However, keratinocyte attachment was enhanced in the DFCM-KM group, where it was 1.24, 1.27, and 1.32 times higher of cells concentration for the ≥18–35-, 36–54-, and ≥55-year age groups, respectively, as compared to the control group. The keratinocytes from each age group demonstrated a similar growth profile for all culture conditions, where the DFCM-KM group exhibited a comparable growth rate with the control group whilst the DFCM-FM group exhibited a significantly lower growth rate compared to the other groups. In contrast, the DFCM-FM group demonstrated a significantly higher healing rate in all age groups as compared to the DFCM-KM and control groups. However, there was no significant difference between the healing rates of the DFCM-KM and control groups. In conclusion, DFCM-KM enhanced keratinocyte attachment while DFCM-FM enhanced the keratinocyte healing rate irrespective of donor age, which indicated the potential application of DFCM in wound healing in aged skin.